Clinical benefits of preemptive oral clonidine versus oral tramadol for abdominal hysterectomy conducted under subarachnoid block with 0.5% hyperbaric bupivacaine: a comparative evaluation - Gupta, Kumkum; Sharma, Swati; Gupta, Prashant K.; Kaur, Guljeet; Tyagi, Vasundra; Makroo, Bilal Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: Neuraxial techniques possess many benefits for elective abdominal hysterectomy due to profound surgical anesthesia and muscle relaxation. The present study was aimed to compare the clinical benefits of pre-emptive oral clonidine with oral tramadol for abdominal hysterectomy conducted under subarachnoid block with 0.5% hyperbaric bupivacaine. Methods: Sixty adult female patients of American Society of Anaesthesiologists (ASA) physical status I and II, aged 42 to 65 years, were randomized into two groups of 30 patients each to receive either oral clonidine, 100 µg (Group C) or oral tramadol 50 mg tramadol (Group T), 90 min before initiation of subarachnoid block with 3.5 mL of 0.5% hyperbaric bupivacaine. Intraoperative hemodynamic changes, duration of analgesia and incidence of shivering were recorded as primary end points. Drug related effects of pruritus, sedation, nausea, vomiting, and respiratory depression were recorded as secondary outcomes. Results: The onset of sensory and motor block was comparable between the groups but the time to two dermatome regression were prolonged in patients of Group C with statistical significant difference (p=0.05). Duration of analgesia was also enhanced in patients of Group C (268.27±12.18 min versus 223.15±14.31 min in Group T) with statistically highly significant difference (p=0.000). The incidence of shivering was lower in the patients of clonidine group. The heart rate was lower in patients of clonidine throughout intraoperative period and no incidence of bradycardia, hypotension or sedation occurred in any patient. Conclusions: Both drugs showed clinical benefits as pre-emptive oral medication for abdominal hysterectomy conducted under subarachnoid block but oral clonidine (100 µg) proved to be more beneficial.